Mexico - Financial Sector Assessment Program Update : Technical Note on Strategic Issues in Development Bank Reform - World Bank; International Monetary Fund (Washington, DC : World Bank, 2022)
State ownership in financial intermediation in Mexico has continued to be significant in qualitative as well as quantitative terms, with about 20-25 percent per cent of the total credit of the banking system provided by development banks (DBs) and funds during the last five years. The importance of government ownership in financial intermediation is not only quantitative, but qualitative, with influence on key sectors in the Mexican economic development. The 2001 joint World Bank- International Monetary Fund (IMF) Financial Sector Assessment Program (FSAP) that took place in 2001 identified a number of problems related to the operation of DBs in Mexico. Some DBs had unclear mandates or did not live up to their mandates with their activities overlapping among themselves or with the activities of commercial banks. Some of them were performing quasi-fiscal activities outside the scope of the budget process, and all of them were loss making even after several rounds of recapitalization. Their operation was often inefficient with high costs, too many employees, and weak internal controls. Fiscal subsidies involved in their operations were not well targeted and were channeled in a non-transparent manner. After the 2001 FSAP assessment the authorities started a reform effort addressing some of the problems mentioned above through legal reforms and tighter monitoring.